Analysis of 24-h Rhythm in Ventricular Repolarization Identifies QT Diurnality As a Novel Clinical Parameter Associated with Previous Ventricular Arrhythmias in Heart Failure Patients - Du Pre, Bastiaan C.; Van Laake, Linda W.; Meine, Matthias; Van der Heijden, Jeroen F.; Doevendans, Pieter A.; Vos, Marc A.; Van Veen, Toon A. B. (Frontiers in Physiology, 2017)
Introduction: Cardiac repolarization abnormalities are among the major causes of ventricular arrhythmias and sudden cardiac death. In humans, cardiac repolarization duration has a 24-hour rhythm. Animal studies show that this rhythm is regulated by 24-hour rhythms in ion channel function and that disruption of this rhythm leads to ventricular arrhythmias. We hypothesized that 24-hour rhythms in QT duration can be used as a predictor for sudden cardiac death and are associated with ventricular arrhythmias. Secondly, we assessed a possible mechanistic explanation by studying the putative role of hERG channel dysfunction. Materials and Methods: In 2 retrospective studies, measures of the 24-hour variation in the QT and QTc intervals (QT and QTc diurnality, QTd and QTcd respectively) have been derived from Holter analyses and compared between groups: 1) 39 post-infarct patients with systolic heart failure (CHF: EF<35 %), of which 14 with, and 25 without a history of ventricular arrhythmias and 2) 5 patients with proven (LQTS2) and 16 with potential (Sotalol-induced) hERG channel dysfunction vs 22 controls. Results: QTd was 2-fold higher in CHF patients with a history of ventricular arrhythmias (38±15ms) compared to CHF patients without VT (16±9ms, p=0.001). QTd was significantly increased in LQT2 patients (43±24ms) or those treated with Sotalol (30±10ms) compared to controls (21±8ms, p<0.05 for both). Discussion: QT diurnality presents a novel clinical parameter of repolarization that can be derived from Holter registrations and may be useful for identification of patients at risk for ventricular arrhythmias.